Hubungan Pengetahuan tentang Inisiasi Menyusu Dini dengan Sikap dalam Memberikan Asi Eksklusif pada Ibu Hamil Trimester III di RSIA Anugrah - Ulfi Wirdariany; Febry Heldayasari Prabandari; Indah Purnamasari (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2025)
Backgroud: Indonesia is ranked third highest in cases of infant mortality. One of the causes of IMR is that babies are given breast milk too late. If all babies were fed only breast milk from the time they were born until the age of 6 months it could save 800,000 lives. Based on data from the West Kalimantan Health Office in 2021, the IMR was 8 per 1,000 births, in 2022 it will be 5.2 per 1,000 births. The aim of the research is to analyze the relationship between knowledge about early initiation of breastfeeding and mothers' attitudes towards providing exclusive breastfeeding to pregnant women in the third trimester at RSIA Anugrah. Methods: The research design used in this research is cross sectional with a quantitative approach. The research population was all pregnant women in the third trimester who had an ultrasound examination at RSIA Anugrah in August 2024, totaling 532 respondents. The sampling technique in this research used a purposive sampling technique with a sample size of 58 respondents. Test the hypothesis using the Chi Square test. Results: Analysis shows that 32 respondents (55.2%) have good knowledge and 50 respondents (86.2%) have a positive attitude. Based on the results of the chi square statistical test, it shows that the p value = 0.000 < p value = 0.05, which means there is a relationship between knowledge about early initiation of breastfeeding and attitudes towards providing exclusive breastfeeding to pregnant women in the trimester III at RSIA Anugrah. Conclusion: Knowledge about early initiation of breastfeeding has a significant relationship with attitudes towards providing exclusive breastfeeding to pregnant women in the trimester III at RSIA Anugrah.